Methodology of treatment of remediation of mining environment passives from Cerro El Toro de Huamachuco for the sustainable development - Flores, Silvana (2019)
The Study proposes the implementation of a clean technology to treat Mining Environmental Liabilities (MELs) from the tailings of all the regions of the country based in study from the tailing pond from Cerro El Toro located in the district of Huamachuco, Province of Sánchez Carrion, Department of La Libertad, which generating contamination of the communities of Shiracmaca and Coigobamba. In that sense, this study aims to provide a methodology based on the Integral Treatment Remediation Method-MRTI-SLFCH that has implemented the integral treatment of detoxification of pollutants in metallurgical tailings that includes the development of the methodologies of the flotation and gravimetric concentration techniques, which are characterized by the use of remediating agents. In order to achieve maximum recovery of heavy metals such as: barium, cadmium, mercury and lead regulated by the Standard of Environmental Quality of the Soil (ECA SOIL) that manages to convert detoxified tailings into construction aggregates to manufacture the ecotechnological bricks. It should be noted that the study was financed by the Innovate Peru Program and with the co-financing of Green Metallurgy Technologies S.R.L.